Synergism between coherent precipitation strengthening and FCC-HCP type transformation-induced plasticity - Dong Huang; Yanxin Zhuang (Materials & Design, 2022)
It is becoming a trend that many strengthening methods are applied at the same time to overcome the strength-ductility trade-off. However, the combination of precipitation strengthening and transformation-induced plasticity (TRIP) is rarely used effectively because precipitates will hinder phase transformation. In this work, the coherent precipitation strengthening of L12 phase and Face-Centered Cubic (FCC) - Hexagonal Close-Packed (HCP) type martensitic transformation are combined in a single alloy. With the synergistic effect of both sides, the yield strength of aged Co52Cr30Ni12Al3Ti3 alloy is increased from 437 MPa (annealed alloy with TRIP effect only) to 715 MPa, while retaining a uniform elongation of more than 50% at room temperature. Further research shows that whether L12 phase exist will directly affect its deformation mode. In the tensile process of aged Co52Cr30Ni12Al3Ti3 alloy, the deformation mode of grains without L12 phase will change from previous stacking fault-predominant deformation to the final transformation-induced plasticity. For the regions where L12 phase exists, martensitic transformation is difficult to occur due to the blocking effect of L12 on stacking fault.